2017
DOI: 10.1002/ajmg.a.38250
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking outcomes in the Neonatal Intensive Care Unit: Cytogenetic and molecular diagnostic rates in a retrospective cohort

Abstract: Genetic disease and congenital anomalies continue to be a leading cause of neonate mortality and morbidity. A genetic diagnosis in the neonatal intensive care unit (NICU) can be a challenge given the associated genetic heterogeneity and early stage of a disease. We set out to evaluate the outcomes of Medical Genetics consultation in the NICU in terms of cytogenetic and molecular diagnostic rates and impact on management. We retrospectively reviewed 132 charts from patients admitted to the NICU who received a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 20 publications
1
35
0
1
Order By: Relevance
“…We have shown that while these high-risk neonates embark on their genetic diagnostic odyssey within the first week of life, the turnaround time for most genetic tests, consistent with prior data 13 , 19 , is typically on the order of several weeks to months. The diagnostic odyssey can therefore last for months (or years) owing to the usual stepwise structure of the traditional genetic diagnostic evaluation, where subsequent rounds of testing are sent only after prior testing has been unrevealing.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We have shown that while these high-risk neonates embark on their genetic diagnostic odyssey within the first week of life, the turnaround time for most genetic tests, consistent with prior data 13 , 19 , is typically on the order of several weeks to months. The diagnostic odyssey can therefore last for months (or years) owing to the usual stepwise structure of the traditional genetic diagnostic evaluation, where subsequent rounds of testing are sent only after prior testing has been unrevealing.…”
Section: Discussionsupporting
confidence: 84%
“…Rapid whole genome sequencing in critically-ill newborns and infants has been demonstrated to have a diagnostic yield as high as 50–70% 14 17 in a research setting, and a recent retrospective analysis found a diagnostic yield of 36.7% using clinical whole exome sequencing 18 . There is a paucity of information regarding the traditional genetic diagnostic evaluation in the NICU, with one prior study showing a diagnostic yield of 26% for infants who had their initial genetic consultation while in the NICU, though most were diagnosed after NICU discharge 19 . However, NICU infants, particularly non-survivors, could benefit immensely from an expeditious genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to admissions to the NICU, a retrospective review of 132 patients admitted to the NICU over a 2‐year period found that 26% (34/126) were ultimately diagnosed with a genetic condition (Malam et al, ). When considering admissions to a PICU, 5.7% (47/821) corresponded to patients with monogenic or chromosomal disorders, while an additional 4% to patients with congenital anomalies (FitzPatrick, Skeoch, & Tolmie, ).…”
Section: Resultsmentioning
confidence: 99%
“…Rare disease contributes significantly to the mortality and morbidity of newborns admitted to the neonatal intensive care unit (NICU) (Berger & Hofer, ; MacDorman, Mathews, & Centers for Disease Control and Prevention (CDC), 2013). These typically complex conditions often have an underlying chromosomal or single gene cause; however, most newborns will not receive a timely genetic diagnosis during their hospital admission and early life (Malam et al, ). This represents a missed opportunity as these infants may not receive the medical or surgical management to maximize outcomes, or have appropriate surveillance plans initiated to minimize the later burden of disease.…”
Section: Molecular Diagnoses In a Cohort Of 20 Newborns Admitted To Tmentioning
confidence: 99%